THE FUNCTION OF SALIVA IN CARIES PREVENTION - Ni Luh Putu Kertiasih; I Made Budi Artawa (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2015)
Saliva has function os the protector of caries. The functions of saliva are as a mechanical cleaner, help the mastication process, swallow process and digestive process. The goals of this paper is to know the function of saliva to prevent caries. This experiment used descriptive method which done by literature study. The problems was answered through studies with exploration from literatures from some books, last experiments and journals which has relation with the problem.Result and discussant this experiment shows that saliva consist of enzymes and minerals to hamper the caries happens, because this enzymes is bacteriostatic. The mineral in saliva is necessary to re-mineralizes the teeth emails. The high volume of saliva can clean the food rest which can make caries likes cariogenic foods. Secretion of saliva gives optimum protection in the prevention of caries, is it because the bacteria in the oral cavity do not have chance to stick on the teeth. Saliva bufer regulate the degree of acidity (pH) in the oral cavity which is a necessary factor and has function in prevention of caries. The ability of saliva to prevent the caries influented by the composition, volume, secretion, and saliva bufer.The conclusion of this experiment are (1) Saliva has function to protect the teeth and the other mouth mucosa. (2) The volume of saliva can make the oral cavity wet so the sticking foods rest which can make caries can be prevented. (3) The high secretion of saliva has function as the mechanic cleaner to hamper the production of microorganism and can prevent caries. (4) Saliva bufer can neutralizes acid and alkalis so the pH in the oral cavity still constant, that situation can hamper caries. Then can be given some advices there are (1) Mastication of the food must uses both of the mandible so the function of the saliva can be maximal. (2) For the society please consumes the foods which have hard texture and fibrous so when the power of mastication is high the secretion of the saliva will be much higher. (3) Do the right thing to stop the chain of the caries which has relation with the saliva so the saliva can be functioned well in hamperand prevent the process of caries.